2014
DOI: 10.3390/ijerph111010824
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence ATP Monitoring for the Routine Assessment of Food Contact Surface Cleanliness in a University Canteen

Abstract: ATP bioluminescence monitoring and traditional microbiological analyses (viable counting of total mesophilic aerobes, coliforms and Escherichia coli) were used to evaluate the effectiveness of Sanitation Standard Operating Procedures (SSOP) at a university canteen which uses a HACCP-based approach. To that end, 10 cleaning control points (CPs), including food contact surfaces at risk of contamination from product residues or microbial growth, were analysed during an 8-month monitoring period. Arbitrary accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…Due to adhesion mechanisms bacteria can remain on the surfaces and contaminate other foods [9]. Chopping boards, knifes and preparation tables are just some of the food preparation instruments found contaminated with bacteria [10].…”
Section: Food Contact Surfacesmentioning
confidence: 99%
“…Due to adhesion mechanisms bacteria can remain on the surfaces and contaminate other foods [9]. Chopping boards, knifes and preparation tables are just some of the food preparation instruments found contaminated with bacteria [10].…”
Section: Food Contact Surfacesmentioning
confidence: 99%
“…The suggested minor role of bacteria as the source of ATP in hygiene monitoring as can be deduced from the present study is to some extent supported by investigations from food processing surfaces. Some studies from the food production show a correlation between ATP bioluminescence and bacterial counts on surfaces (Osimani et al ; Hammons et al ), while a poor correlation is observed in other studies (Poulis et al ; Moore and Griffith ). It was observed that the bacteria usually dominating in fish processing plants had higher ATP values than the pathogenic bacterium L. monocytogenes .…”
Section: Discussionmentioning
confidence: 96%
“…Baker's yeast (10 g) was diluted in sterile peptone‐saline solution and then ten‐fold diluted in the same solution; aliquots (0.1 mL) of each dilution were used for counting yeasts on modified YEPD agar (as described above). Moreover, 10 g of the same sample underwent enrichment in 90 mL of YEPD broth (yeast extract 10 g L −1 ; peptone 10 g L −1 ; d ‐glucose 20 g L −1 ) with 100 mg L −1 of chloramphenicol, incubated for 5 days at 25 °C and then streaked on modified YEPD agar and incubated again for 5 days at 25 °C.…”
Section: Methodsmentioning
confidence: 99%